Determinants of Sharia Stock Investment Decisions: The Role of Investment Interest and Financial Behavior - Bastian, Adol; Aidil Novia,; Meirison, (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
The significant increase in investor participation in the sharia capital market, especially among the younger generation, requires an understanding of the factors that influence investment decisions. This study aims to examine the effect of financial literacy, risk perception, and herding behavior on sharia stock investment decisions, with interest as a mediating variable and financial behavior as a moderating variable. The method used is a quantitative approach with primary data from 391 active investors of PT FAC Sekuritas Indonesia Jambi Branch. Sampling using purposive sampling, and analysis was carried out through SEM-PLS with SmartPLS 4. The results of the study indicate that financial literacy, risk perception, and herding behavior have a significant positive effect on investment interest. Interest fully mediates the relationship between financial literacy and risk perception on investment decisions. Conversely, the direct influence of both is not significant. Herding behavior also has a significant direct effect on investment decisions, but is partially mediated by interest. Financial behavior does not significantly moderate the tested relationship. These findings indicate that interest and social influence are more decisive in determining sharia investment decisions than rationality alone, so that the investor education approach needs to combine psychological and social aspects.